1998
DOI: 10.1016/s0002-9270(98)00587-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hospital mortality in cirrhotic patients: comparison of child-pugh and acute physiology, age and chronic health evaluation (APACHE III) scoring systems

Abstract: The APACHE III scoring system is superior to Child-Pugh for prognosticating short term survival of cirrhotic patients. Prognostic accuracy of APACHE III can be enhanced by incorporating information regarding ascites and prothrombin time prolongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Because mathematical equations for APACHE III have not been published and for APACHE II this equation is available only for admission, these equations have not been used to calculate the relative risk of death. In agreement with other studies [34,35,37,39,40], we wanted to test the accuracy of single-score values. Patients admitted to a medical ICU during the first 24 hours of their presentation were excluded from our study, thus resulting in a mortality rate of only 11.5%.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Because mathematical equations for APACHE III have not been published and for APACHE II this equation is available only for admission, these equations have not been used to calculate the relative risk of death. In agreement with other studies [34,35,37,39,40], we wanted to test the accuracy of single-score values. Patients admitted to a medical ICU during the first 24 hours of their presentation were excluded from our study, thus resulting in a mortality rate of only 11.5%.…”
Section: Discussionmentioning
confidence: 75%
“…Butt et al reported that by using discriminant analysis, APACHE III score correctly classified 75% of cases vs. 67% of cases for Child-Pugh score [40]. No cutoff values were reported, the overall model calibration was not tested and data from blood gas analysis were not included in the calculation of the APACHE III score, thus resulting in an incomplete score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When admitted to an ICU, mortality for patients with cirrhosis is high [3]; recent data suggest greater than 37% ICU mortality and 49% hospital mortality [4,5]. Because of the poor odds for recovery despite aggressive interventions, several investigators have examined how scoring systems may be used to predict outcome and allocate resources in this cohort of ICU patients [6,7]. Much of this effort has focused on determining whether organ-specific scoring systems outperform traditional ICU scoring systems in predicting the risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…1–4 The CTP currently used is calculated from 5 subscores, 3 based on objective clinical laboratory values, total bilirubin, serum albumin, and international normalized ratio (INR) and 2 subjective variables quantifying the severity of ascites and hepatic encephalopathy (HE) from none to mild (or medically controlled) to severe (or medically refractory). Although highly predictive of surgical risks, 5–9 hospital mortality, 10,11 post-transcatheter arterial embolization mortality, 12,13 transplantation waitlist mortality, 14 and long-term survival 15 in cirrhosis, its major limitations are the dependence on subjective variables and arbitrary laboratory cut points that have never been formally validated. 4 Because of the subjective nature of 2 of the CTP variables, it is challenging, time-consuming, and costly to manually extract all data required to calculate the CTP from historical data.…”
mentioning
confidence: 99%